2013
DOI: 10.5402/2013/581027
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Recommended Breast Cancer Screening in Iranian Turkmen Women: The Role of Knowledge and Beliefs

Abstract: The aim of the current study was to investigate breast cancer screening performance among Iranian Turkmen women along with their knowledge and beliefs. A cross-sectional study was carried out in June to December 2011. Through clustered sampling method, 1080 Iranian Turkmen women completed the questionnaire including breast cancer screening adherence, knowledge, fatalism beliefs, and perceived threat using Champions Health Belief Model Scale (CHBMS).The mean age of the participants was 43.04 (SD = 11.80) years.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
39
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 31 publications
4
39
3
Order By: Relevance
“…For example, as reported in the study by Wang et al (2009) Chinese women were less interested in going for a mammography because the traditional method of cancer prevention promotes maintaining a balanced diet, using herbs, and exercising as the best approach (Wang et al, 2009). Likewise, diversity in individual and sociocultural environment such as cultural affiliation (Yu and Wu, 2005), lack of health services (Yu and Wu, 2005;Gomez et al, 2007;Gao et al, 2012), low perceived awareness (Yu and Wu, 2005;Gomez et al, 2007;Lee-Lin et al, 2007), or low educational level (Lee-Lin et al, 2007), fatalistic attitude (Charkazi et al, 2013), and low perceived risk of breast cancer (Kim et al, 2011) were found to affect the attendance on screenings. Using the Health Belief Model (HBM), screening practices are one of the health promotion behaviors (Lee-Lin et al, 2008;Kim et al, 2011;Charkazi et al, 2013).…”
Section: Factors Associated With Mammography Adherence Among Married mentioning
confidence: 99%
See 2 more Smart Citations
“…For example, as reported in the study by Wang et al (2009) Chinese women were less interested in going for a mammography because the traditional method of cancer prevention promotes maintaining a balanced diet, using herbs, and exercising as the best approach (Wang et al, 2009). Likewise, diversity in individual and sociocultural environment such as cultural affiliation (Yu and Wu, 2005), lack of health services (Yu and Wu, 2005;Gomez et al, 2007;Gao et al, 2012), low perceived awareness (Yu and Wu, 2005;Gomez et al, 2007;Lee-Lin et al, 2007), or low educational level (Lee-Lin et al, 2007), fatalistic attitude (Charkazi et al, 2013), and low perceived risk of breast cancer (Kim et al, 2011) were found to affect the attendance on screenings. Using the Health Belief Model (HBM), screening practices are one of the health promotion behaviors (Lee-Lin et al, 2008;Kim et al, 2011;Charkazi et al, 2013).…”
Section: Factors Associated With Mammography Adherence Among Married mentioning
confidence: 99%
“…Likewise, diversity in individual and sociocultural environment such as cultural affiliation (Yu and Wu, 2005), lack of health services (Yu and Wu, 2005;Gomez et al, 2007;Gao et al, 2012), low perceived awareness (Yu and Wu, 2005;Gomez et al, 2007;Lee-Lin et al, 2007), or low educational level (Lee-Lin et al, 2007), fatalistic attitude (Charkazi et al, 2013), and low perceived risk of breast cancer (Kim et al, 2011) were found to affect the attendance on screenings. Using the Health Belief Model (HBM), screening practices are one of the health promotion behaviors (Lee-Lin et al, 2008;Kim et al, 2011;Charkazi et al, 2013). According to the HBM, people who believe that a course of action will produce positive outcomes or perceive barriers in engaging in the course action are more likely to participate in health behavior practices (Charkazi et al, 2013).…”
Section: Factors Associated With Mammography Adherence Among Married mentioning
confidence: 99%
See 1 more Smart Citation
“…It is discussed that the low effectiveness and utility of interventions may be linked to a lack of awareness concerning the mechanisms in charge for BC screaming behaviors. In the last decade, the importance placed on theory when planning interventions has increased (Moodi et al, 2012;Charkazi et al, 2013;Yoo et al, 2013). While researchers frequently refer to a theoretical framework (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Iranian women are at a mostly high risk for relapse of breast cancer due to lack of appropriate knowledge (Thomas et al, 2011;Samah and Ahmadian, 2012;Charkazi et al, 2013), cancer fear (Lamyian et al, 2007;Heidari et al, 2008;Babu et al, 2011), social manners (Taymoori et al, 2012;Charkazi et al, 2013), painful mammography (Taymoori et al, 2013), embarrassing, and those constraints related to health care and insurance systems (Keshavarz et al, 2011;Fouladi et al, 2013). Iranian women have also particular social beliefs that may influence motivation for preventive medicine, such Parvaneh Taymoori 1 *, Mahdi Moshki 2 , Daem Roshani 3 as cultural beliefs, fatalism, and devoting themselves over the family as they get older (Lamyian et al, 2007;Taymoori et al, 2012).…”
Section: Introductionmentioning
confidence: 99%